Refining the definitions of cultural safety, cultural competency and Indigenous health: lessons from Aotearoa New Zealand - Elana Curtis; Belinda Loring; Rhys Jones; David Tipene-Leach; Curtis Walker; Sarah-Jane Paine; Papaarangi Reid (International Journal for Equity in Health)
Abstract Eliminating Indigenous and ethnic health inequities requires culturally-competent and culturally-safe health workforces and systems. Health professional training institutions and regulatory bodies are increasingly including cultural competency and cultural safety in health professional accreditation standards, and pre-service and in-service training programmes. However, there are mixed definitions and understandings of cultural competency and cultural safety, and how best to achieve them. In 2019, we published a review of international understandings of these terms, and proposed an Indigenous-led definition for cultural safety that we believed to be more fit for purpose in achieving health equity. We also clarified essential principles and practical steps to operationalise this approach in healthcare organisations and workforce development. The aim of this paper is to share our expert reflections upon the experience over the six years since 2019, of implementing this definition in an Aotearoa New Zealand (NZ) context. Recent work undertaken with health regulatory bodies in NZ to refine the understandings of cultural competency, cultural safety and Indigenous health has extended our positioning on these important concepts. A practical example of how these related but distinct concepts apply to Indigenous health is presented.